Bagaimana Lingkungan Membentuk Karakter Dan Sikap Kita - Naila Rahma Aulia; Ellen Prima (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The living, social, and cultural environment plays a crucial role in shaping an individual's identity. This article aims to analyze how external environmental factors influence the formation of human character and attitudes in daily life. The method used in this study is a literature review, which involves collecting, filtering, and analyzing data from various relevant scientific journals, books, and social psychology research findings. The results of the analysis indicate that the family e`nvironment acts as the primary foundation for early character development, while the school and peer environments expand an individual's social attitude adaptation. Furthermore, exposure to culture and modern digital media is proven to accelerate shifts in mindsets and behavioral responses. In conclusion, our character and attitudes are not entirely innate, but rather the dynamic result of constant interaction with our surroundings. Therefore, creating a positive environment is highly recommended to build a generation with strong character and healthy attitudes.